Perbedaan Kadar Tumor Necrosis Factor - Alfa Antara Diabetes Mellitus Tipe 2 Terkontrol Dengan Tidak Terkontrol - Elsa Yuniarti (UNIVERSITAS NEGERI PADANG, 2017)
Hyperglicemia in DM Type will induce macrofag to produce cytokin proinflamation TNF-α. High levels of TNF-α in DM Type 2 can lead to more severe insulin resistance and become involved in endothelial dysfunction which lead to complications of the disease. This research aims to know differences between TNF-α level in DM type 2 controlled and uncontrolled. This research used obervational analizing method and cross sectional study comparative approach. Blood samples are grouped to 35 patient DM type 2 controlled and uncontrolled in the medicinal treatment in Padang State University polyclinic. The level of serum TNF-α will be examined in Biomedical Laboratory FKUA using ELISA method. TNF-α level in the diabetes type 2 controlled on average 7,55 ± 0,43 pg/ml whereas uncontrolled on average 149,28 ± 26,82 pg/ml. The Mann-Whitney test showed a p value < 0,001. There are significant differences in the levels of TNF-α in patients with DM type 2 controlled and uncontrolled. Key Words : Diabetes Mellitus type 2 controlled and uncontrolled, TNF-α